Dutch Colonialism and Imperialism on the Economic Condition of the Indonesian People - Sukarddin, Sukarddin; Hidayati, Sri Wahyu (UNIVERSITAS MUHAMMADIYAH METRO, 2024)
The purpose of this research is to find out more about the process of the arrival of Western nations to Indonesia, especially the beginning of the arrival of the Dutch in Indonesia, namely to monopolize trade, especially spices in the archipelago which was handed over to the Dutch government when the VOC went bankrupt, besides that we all will know the impact of colonialism and imperialism carried out by the Dutch East Indies government on the economic growth of the Indonesian people from 1596-1900. The methods used are historical, heuristic, verification, interpretation and historiography methods. The results of this research can find out about the motives for the arrival of Westerners to Indonesia, namely the same as the aim of other countries, namely to monopolize the spice trade in the archipelago, but the VOC was officially disbanded in 1799 with a total debt of 134.7 million guilders to Dutch government, and in return the VOC's territory was taken by the government. Starting from that year, Indonesia was officially directly under the authority of the Dutch government with representatives of the Dutch East Indies government. In implementing Dutch colonialism and imperialism, they used several very detrimental methods, namely: Culturstelsel, liberal colonial agrarian law.